The contestation of the sensible under populist authoritarianism: between silencing and seeking democratic rights - Gündüz Arabaci, Çisem (Frontiers in Political Science, 2025)
Populist authoritarian leaders systematically undermine democratic foundations primarily through manipulating election processes and eroding the judicial institutions. Veiled in the rhetoric of “the will of the people”, their ostensibly legal yet fundamentally rights-violating actions relentlessly constrict the political and social realms, forcing individuals into fierce defense of even their most basic human rights. This study employs conceptual and interpretive analysis grounded in the works of Hannah Arendt (realm of political action), Sheldon Wolin (managed democracy), Carl Schmitt (state of exception), Micheal Foucault (e.g., biopolitics), and Jacques Ranciere (e.g., “partage du sensible” (the distribution the sensible), polis order). The research examines how populist leaders leverage authoritative motives to render individuals invisible within a constructed and unjustifiable order. The study argues that social uprisings are pivotal moments in which the existing “the distribution of the sensible” is critically challenged by people’s unexpected and irruptive affirmations of equal capacity. These social reactions not only complicate existing discussions concerning democratic theory but also offer a novel framework for understanding the evolving forms of political subjectification in an era of global autocratization.